Resourcification: A non‐essentialist theory of resources for sustainable development. (14th June 2021) - Corvellec, Hervé; Hultman, Johan; Jerneck, Anne; Arvidsson, Susanne; Ekroos, Johan; Wahlberg, Niklas; Luke, Timothy W.
Abstract: Overuse of resources is accelerating current negative trends in climate change, ecosystem destruction, and biodiversity loss. The ultimate outcome is that contemporary human society is reaching or exceeding the limits of planetary boundaries. It is therefore imperative to articulate a new theoretical understanding of resources and the ethical, political, and environmental conditions of their use. In this article, we take a radical departure from treating resources as having fixed, essential and ready to exploit qualities, and offer a non‐essentialist theory that considers that resources come into being as a result of social processes. We label this approach resourcification . This shift offers a new theoretical platform for developing a post‐sustainability understanding of the relationships of humans to humans, to other living creatures, and to the physical environment, one that is more suited to meeting the challenges of working with the sustainable development goals in the Anthropocene.